Controlled preparation of CaO adsorbents by microsyringe titration technology for CO2 capture. Issue 4 (24th July 2022) - Wu, Jialin; Liu, Xuan; Zhang, Rumeng; Wu, Zhaojun; Zhang, Jianbin
Abstract: CaCO3 precursors were prepared by a simple titration method by dropping CaCl2 solution into a CO2 storage material (CO2 SM) solution using a syringe pump; afterward, the precursors were roasted at 900°C to form CaO adsorbents for CO2 adsorption at 750°C for 2 h. Subsequently, the CO2 SM dosage, CaCl2 concentration, drip speed, temperature, and stirring speed were systemically optimized by designing single‐factor experiments. Further, a three‐factor and three‐level response surface experiment was designed to investigate the interactions among the factors according to their effects on CO2 adsorption. After optimizing the preparation conditions, the CO2 adsorption capacity reached 739.6 mg/g. Fifteen adsorption cycles were conducted on the adsorbent under the optimal preparation conditions, and the adsorption performance was reduced by 52.8%. Finally, the formation mechanism of CaCO3 and the CO2 adsorption processes of CaO were discussed using a Fourier‐transform infrared spectrometer (FTIR), X‐ray diffractometer (XRD), scanning electron microscope (SEM), and high‐resolution transmission electron microscope (HR‐TEM). © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.